Cover Image. (14th December 2018) - Chandraprakash, Kumarasamy; Vandana, Nandakumar; Sankaran, Mathan; Uvarani, Chokkalingam; Ata, Athar; Mohan, Palathurai Subramaniam; Suresh, Thangaraj
Abstract : The cover image is based on the Article Microwave‐assisted Synthesis of Dihydro Dibenzophenanthroline and Its Derivatives Using a Self‐catalyzed Friedlander Reaction, by Suresh Thangaraj et al., https://doi.org/10.1002/jhet.3339 .